ANALISIS STRUKTUR PENERIMAAN DAERAH DAN PERGESERAN SEKTOR EKONOMI UNGGULAN KABUPATEN KAMPAR TAHUN 2010 – 2019 - Nurmala Sari; Sri Endang Kornita; Hendro Ekwarso (Program Studi Pendidikan Ekonomi Universitas Riau, 2021)
The purpose of this study is to determine the structure of regional revenues and analyze the shift in leading sectors in Kampar Regency from 2010 to 2019. The data used are the Central Statistics Agency of Kampar Regency, the Central Statistics Agency of Riau Province, the Regional Development Planning Agency and other sources such as the internet and literature study. The analysis was carried out with a descriptive method using a quantitative approach. In this study using location quetient (LQ) analysis tools, shift share, typology class. The results of the analysis show that Kampar Regency in running its government and its economy still depends on the transfer of central government funds and the analysis also shows a shift in the leading sectors in Kampar Regency, such as the manufacturing sector and the health service sector and social activities from 2010 to 2014 2015 - 2019.